IMPLEMENTASI PEMBELAJARAN SEJARAH SASTRA INDONESIA BERBASIS PROYEK DI MASA PANDEMI - Silvia Utami; Ahmad Bahtiar (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the implementation of project-based learning of Indonesian Literary History during the pandemic. This study uses quantitative-experimental research methods to be able to explore how effective this method is if implemented within the scope of learning. This method provides opportunities for lecturers to manage learning in class by involving project work. In this course, there are three work projects applied, namely: (1) students make infographics in groups which will be presented every meeting; (2) students make a book chapter which will later at the end of the semester be made into a book; and finally (3) students make a scientific publication in the form of journal articles which later must be submitted to national journals. The object of this research is a 2nd semester student of the Indonesian Language and Literature Education study program at Syarif Hidayatullah State Islamic University Jakarta. So, it can be concluded that the project method applied in learning literary history in the Modern Indonesian Literature History course Semester 2 of Syarif Hidayatullah State Islamic University Jakarta is an effective learning method applied during a pandemic.